Pictorial Metaplan as a Teaching aid to Improve Speaking Skills in Junior High School Students - Saptanto, Deswandito Dwi; Bowo, Tri Arie; Nurjanah, Ratih Laily (Universitas Negeri Semarang, 2021)
This study focuses on improving students’ abilities in learning English with the support of Pictorial Metaplan as a teaching aid. The use of this Metaplan aims to improve speaking skills in formal and non-formal contexts. This pictorial Metaplan is a realia in the form of an illustrated carpet with a theme Getting Direction. Pictorial Metaplan focuses on the topic Getting Direction and applied directly to 15 students in the 8th grade of junior high school. The implementation of the use of the Pictorial Metaplan begins with distributing questionnaires and implementing Pre- Test and Post-Test, then direct implementation of using Pictorial Metaplan combined with Total Physical Response (TPR) method. The treatment for students was carried out by dividing two class groups, the control group, and the experimental group. The control group used conventional methods, without using learning aids, while the second group used the Pictorial Metaplan as a teaching aid. Based on the results of Pre-Test and Post-Test show an increase in the results of the values before and after implementing the Pictorial Metaplan. Thus it can be concluded that learning in the experimental group using Pictorial Metaplan is more effective than learning using conventional methods.